2010
DOI: 10.1016/j.neuron.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Native Functions of the Androgen Receptor Are Essential to Pathogenesis in a Drosophila Model of Spinobulbar Muscular Atrophy

Abstract: Summary Spinobulbar muscular atrophy (SBMA) is a neurodegenerative disease caused by expansion of a polyglutamine tract in the androgen receptor (AR). This mutation confers toxic function to AR through unknown mechanisms. Mutant AR toxicity requires binding of its hormone ligand, suggesting that pathogenesis involves ligand-induced changes in AR. However, whether toxicity is mediated by native AR function or a novel AR function is unknown. We systematically investigated events downstream of ligand-dependent AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
176
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(196 citation statements)
references
References 75 publications
12
176
3
Order By: Relevance
“…While signs of androgen insensitivity are sometimes seen in SBMA, the disease is not due to a loss of AR function but rather to a gain of a toxic property of the mutant polyglutamine-expanded androgen receptor. Although the precise mechanistic pathway leading to AR misfolding, aggregation, and its subsequent toxicity has not been fully elucidated, it is known that binding of one of the natural AR ligands, testosterone or 5␣-dihydrotestosterone, and nuclear localization are required for both motor dysfunction and neuropathology (9,11,12).…”
mentioning
confidence: 99%
“…While signs of androgen insensitivity are sometimes seen in SBMA, the disease is not due to a loss of AR function but rather to a gain of a toxic property of the mutant polyglutamine-expanded androgen receptor. Although the precise mechanistic pathway leading to AR misfolding, aggregation, and its subsequent toxicity has not been fully elucidated, it is known that binding of one of the natural AR ligands, testosterone or 5␣-dihydrotestosterone, and nuclear localization are required for both motor dysfunction and neuropathology (9,11,12).…”
mentioning
confidence: 99%
“…The pathogenesis of polyQ diseases is complex, but it has been suggested that the expanded polyQ protein causes disease through a toxic gain-of-function mechanism. More recently, protein context and normal protein activity have been shown to be critical in the pathogenesis of these diseases (4,5). In SCA6, the CAG repeat encodes a polyQ tract in the cytoplasmic tail domain of the Ca v 2.1 channel, a pore-forming subunit of the P/Q type voltage-gated calcium channels (6).…”
mentioning
confidence: 99%
“…Large-scale and candidate-based genetic-modifier screens have been extremely successful in revealing pathways novel to polyQ disease protein toxicity (Fernandez-Funez et al 2000;Kazemi-Esfarjani and Benzer 2000;Bilen and Bonini 2007;Nedelsky et al 2010). Examples include a large-scale EP screen for polyQ modifiers that revealed new roles for microRNAs (miRNAs) in maintaining the integrity of the nervous system (Bilen et al 2006;Liu et al 2012).…”
Section: Genome-wide Screens To Define Modifier Playersmentioning
confidence: 99%